Instrumentalidade do serviço social: dimensões teórico-metodológica, ético-política e técnico-operativa e exercício profissional - Costa, Francilene Soares de Medeiros (2008)
The dissertation proposes a discussion about the instrumentality of the Social Work, in the attempt of visualizing her, as well as the profession, in a totality perspective to the light of the rationality critical-dialetical. Understood as the capacity that the professional subjects acquire of giving answers to the demands that are placed to the profession, itself built partner-historically, in a teleologys conflicts and causalitys. So, it is proposed the discussion of the instrumentality while a group of you know specific, composed essentially by the development of three practical-formative dimensions. The theoretical-methodological refers to the capacity of apprehension of the method and of the theories and, consequently, of the relationship that does with the practice. The dimension ethical-politics concerns the development of the capacity of analyzing the society and the own profession as field of contradictory forces, being considered the character eminently political of the professional exercise, as well as the professional's conscience concerning the social direction that prints in your intervention. And the technician-operative dimension refers more strictly to the technical elements and you score for the development of the intervention. It was looked for to evidence as those dimensions they attend in the professional exercise, starting from the experience lived by the social workers of the Social Attendance Reference Centers, in Natal/RN